2001
DOI: 10.1542/peds.108.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Recent Skin Injuries in Normal Children

Abstract: The majority of normal children (after the age of 9 months) and adolescents, who do not consult for trauma, had 1 or more recent skin injuries. These injuries, mostly bruises, are more prevalent in the summer in a region with a temperate climate and can be present on all parts of the body, although they are most frequently observed on the limbs, especially on the shins and knees. Even if there are no recognizable marks on the skin, physicians must pay particular attention to children who have injuries with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 15 publications
1
79
0
2
Order By: Relevance
“…75 There is ample evidence that evaluating bruising patterns in abused and nonabused children helps to identify specific ages, locations, and patterns of bruising that are highly correlated with child abuse. [76][77][78][79][80][81] In children with bruising related to normal activity, the prevalence and mean number of bruises increases with age, and the majority of preschool-aged and schoolchildren have accidental bruises. 82 The commonest sites of bruising in nonabused, ambulatory children are to the knees and shins, and the vast majority of normal bruises are over bony prominences, including the forehead.…”
Section: Skin Injuriesmentioning
confidence: 99%
“…75 There is ample evidence that evaluating bruising patterns in abused and nonabused children helps to identify specific ages, locations, and patterns of bruising that are highly correlated with child abuse. [76][77][78][79][80][81] In children with bruising related to normal activity, the prevalence and mean number of bruises increases with age, and the majority of preschool-aged and schoolchildren have accidental bruises. 82 The commonest sites of bruising in nonabused, ambulatory children are to the knees and shins, and the vast majority of normal bruises are over bony prominences, including the forehead.…”
Section: Skin Injuriesmentioning
confidence: 99%
“…39 Inflicted trauma may be suspected when injuries are noted in protected areas of the body (torso, genitals, neck, medial thighs), 40 when they have a patterned appearance, or when the explanation provided by the patient is incongruous with the injury. 39 Laboratory testing and diagnostic imaging for possible internal injury may be indicated.…”
Section: Victim Identification and Evaluationmentioning
confidence: 99%
“…8 Identifying which children with bruising warrant an evaluation for abuse and SS can be challenging, especially in mobile older infants and toddlers who frequently experience accidental bruising. 14,15 Several studies have identified characteristics of bruises associated with abusive versus accidental injury, but clear guidelines for clinicians regarding when to perform an initial SS for abuse in young children with bruising have not been developed. 1,16 Accordingly, the goal of this study was to develop guidelines for performing initial SS in children ,2 years old presenting with bruising.…”
Section: What This Study Addsmentioning
confidence: 99%